2009
DOI: 10.1007/s12070-009-0053-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of outcome of type I tympanoplasty in dry and wet ear

Abstract: Chronic suppurative otitis media is a common condition seen in patients attending the otolaryngology clinic. The discharging ear presents the otologist with the dilemma of operating on it or not. This due to the widespread belief that the success rate while doing tympanoplasty on wet ears is decidedly inferior. To evaluate this fact we conducted a study to compare outcomes of type 1 tympanoplasty in dry and wet ears. Wet ear meant that the patient had a mild mucoid discharge which was negative on culture. Type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
37
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 1 publication
11
37
3
Order By: Relevance
“…Nagle et al and Bunzen et al found no influence of the condition of the ear at the time of surgery on the subsequent graft take rate which is comparable to our study. 7,8 Histopathology of excised remnant TM in wet ears showed evidence of inflammatory cells and vascularization within stroma of fibroblasts while these were absent in dry ears which is similar to other studies who have postulated that vascularity and inflammation in cases of active COM has influence on graft uptake. 5,9 In this study the overall success rate in graft uptake following myringoplasty was 88.3%, with 86.7% in wet ears and 90% in dry ears.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Nagle et al and Bunzen et al found no influence of the condition of the ear at the time of surgery on the subsequent graft take rate which is comparable to our study. 7,8 Histopathology of excised remnant TM in wet ears showed evidence of inflammatory cells and vascularization within stroma of fibroblasts while these were absent in dry ears which is similar to other studies who have postulated that vascularity and inflammation in cases of active COM has influence on graft uptake. 5,9 In this study the overall success rate in graft uptake following myringoplasty was 88.3%, with 86.7% in wet ears and 90% in dry ears.…”
Section: Discussionsupporting
confidence: 83%
“…There is slight female preponderance (M:F =0.93:1) in our study which is comparable to study by Nagle et al wherein female preponderance was observed with male to female ratio was found to be 0.85:1.36. 7 On considering the side of involvement in tubotympanic COM, perforation was more common on left side (51.9%) with 8 patients having bilateral COM. Nagle et al observed perforation to be common on right side (42%) and with bilateral presentation in 18% of their cases.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…For Nagle, 15 closure rate was 88% for dry ears and 74% for wet ears without a significant difference (p=0.07). A hearing gain rate more than 10 dB was seen in 72% for dry ears versus 60% for wet ears (p=0.85).…”
Section: 6-15mentioning
confidence: 90%